2015
DOI: 10.1007/978-94-017-7342-3_17
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Analyzing the Chemical Mechanisms of Bitumen Aging and Rejuvenation with FTIR Spectrometry

Abstract: The recycling of asphalt is a process where old pavement is broken up and used as reclaimed asphalt pavement (RAP) in new asphalt pavement, often with the aid of recycling agents. The goal of asphalt recycling agents is to reintroduce the properties lost in bitumen and asphalt during aging such as penetration, softening point, viscosity, ductility, cohesion and adhesion to aggregate, reducing the performance of asphalt and requiring its replacement. The purpose of this study is to observe the chemistry of bitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Because of the extreme complexity of bitumen, detailed chemical characterization of aging effects is still an analytical challenge, and therefore, chemical analyses are mostly limited to functional group analysis or fractionation in saturates, aromatics, resins, and asphaltenes (SARA fractionation) . With infrared spectroscopy, the formation of carbonyl as well as sulfoxide functions during oxidative aging has been frequently reported in the literature. , It was shown that sulfoxides are formed with higher reaction rates than carbonyls, and moreover, a temperature dependence of the oxidation reaction was revealed. , SARA fractionation has been used since the 1960s for the chemical description of bitumen . Saturates are considered as almost inert with respect to oxidation, , while resins and asphaltenes show stronger changes. , Petersen et al (2009) ranked the reactivity of the SARA fractions with oxygen in the following order: saturates < aromatics < resins < asphaltenes, while the asphaltene fraction is the most reactive one .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the extreme complexity of bitumen, detailed chemical characterization of aging effects is still an analytical challenge, and therefore, chemical analyses are mostly limited to functional group analysis or fractionation in saturates, aromatics, resins, and asphaltenes (SARA fractionation) . With infrared spectroscopy, the formation of carbonyl as well as sulfoxide functions during oxidative aging has been frequently reported in the literature. , It was shown that sulfoxides are formed with higher reaction rates than carbonyls, and moreover, a temperature dependence of the oxidation reaction was revealed. , SARA fractionation has been used since the 1960s for the chemical description of bitumen . Saturates are considered as almost inert with respect to oxidation, , while resins and asphaltenes show stronger changes. , Petersen et al (2009) ranked the reactivity of the SARA fractions with oxygen in the following order: saturates < aromatics < resins < asphaltenes, while the asphaltene fraction is the most reactive one .…”
Section: Introductionmentioning
confidence: 99%
“…This understanding is especially important due to the changing nature of the way the bitumen is used in pavement (Planche, ). The introduction of Polymer Modified Asphalt (PMA) (Yu et al ., ), Reclaimed Asphalt Pavement (RAP) that incorporates aged binder (Baghaee Moghaddam & Baaj, ), and the development of biosourced agents as both additives (Mikhailenko et al ., ) and standalone binders (Fini et al ., ), means that empirical approaches to asphalt binder in pavement are no longer always viable. Other possibilities are the further understanding of the asphalt binder aging – both field and laboratory simulated – as well as the effects of cold temperature, and of various heating methods.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks around 1460 and 1376 cm −1 are for aliphatic C−CH 3 groups, serving as baselines for the analysis, because they change relatively little during aging. 23 2.2.2. ESEM Analysis.…”
Section: Energy and Fuelsmentioning
confidence: 99%